Materials properties, lattice dynamics and polaron characteristics in InSbxP1-x ternary alloys. (April 2021) - Benyettou, S.; Saib, S.; Bouarissa, N.
Abstract: The structural, elastic and piezoelectric properties of zinc-blende InSbx P1-x ternary alloys are presented. Besides, phonon modes and polaron characteristics are reported. In addition, many thermodynamic quantities in instance, thermal expansion coefficient, heat capacity and entropy are examined and discussed. A reasonably good accord is obtained between our calculated results and those quoted in the literature. The results regarding piezoelectric, thermal and polaron properties dependence on Sb concentration in InSbx P1-x may be seen as the first predictions.